Dual‐band in‐/anti‐phase filtering power dividers. Issue 11 (November 2016) - Qin, W.; Chen, J.‐X.; Zhou, L.‐H.; Bao, Z.‐H.; Xue, Q.
ABSTRACT: This article presents a novel dual‐band in‐/anti‐phase filtering power divider. The signals of the two output ports are symmetrically extracted from the resonator. Naturally, they are in‐phase for even‐mode passband but anti‐phase for the odd‐mode passband. The intrinsic reason is that a negative group delay (NGD) frequency band is presented between the two passbands, which opens a window for the change of the 180º phase differences. For demonstration, a dual‐band filtering power divider is designed and measured based on the stub‐loaded resonators (SLRs). Good agreements are observed between the measured and simulated results, showcasing small magnitude and phase differences in both passbands. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:2626–2629, 2016